A Protocol for Basketball as Inclusive Sport to Boost Motor and Social Skills in Autistic Preschoolers - Annalisa Levante; Chiara Martis; Giuseppe Antonioli; Massimo Dima; Luigia Duma; Marco Perrone; Flavia Lecciso (Disabilities)
This paper presents the Early Basketball Protocol, a sports-based intervention designed to improve motor and socio-emotional skills in autistic preschoolers. Recognizing the paucity of sports protocols for younger autistic children, we developed this protocol using basketball rules to foster an inclusive setting where autistic preschoolers (n = 4) and their typically developing peers (n = 13) could engage in activities together. The protocol aims to simultaneously develop motor and socio-emotional skills through inclusive sports activities. Due to the COVID-19 pandemic, the effectiveness of the protocol was evaluated using parent-reported measures. A narrative approach synthesized the parental answers, and a pre–post-test analysis evaluated the preliminary application of the EB protocol based on parent-reported perceptions. Encouraging longitudinal results emerged, particularly in the improvement of socio-emotional skills for all participants. However, the early disruption of activities due to the pandemic may have contributed to the lack of improvement in gross motor skills. The paper discusses the practical implications of these findings and outlines future research directions, emphasizing the critical role of social inclusion.